Phrasal alternation in the Pondok Tinggi dialect of Kerinci; An intergenerational analysis - Ernanda, Ernanda (UI Scholars Hub, 2015)
This paper examines the implications of language contact in a Malay sub-variety known as Pondok Tinggi, spoken in Sumatra. My focus is on the grammatical phenomenon of phrasal alternation. Phrasal alternation is characterized by the presence of two distinct forms for nearly all lexical items, whose final syllables differ in shape. These are termed absolute and oblique (Steinhauer and Usman 1978: 485). The intergenerational transmission of this uncommon feature offers a way to measure the degree of contact-induced language change in Pondok Tinggi. An experiment was conducted to elicit the usage of the absolute and the oblique forms in order to find out how the distribution of phrasal alternation has changed within the last two generations. I reveal a grammatical simplification caused by contact between Pondok Tinggi and Bahasa Indonesia, a related Malayic variety serving as Indonesia's prestigious official language. This adds a dimension of loss of local linguistic diversity to more familiar tropes of the national success of Bahasa Indonesia.